How Predictable are “Spontaneous Decisions” and “Hidden Intentions”? Comparing Classification Results Based on Previous Responses with Multivariate Pattern Analysis of fMRI BOLD Signals - Lages, Martin; Jaworska, Katarzyna (Frontiers in Psychology, 2012)
In two replication studies we examined response bias and sequential dependencies in binary decisions. We applied a linear classifier (SVM) to predict spontaneous decisions as well as hidden intentions from responses in preceding trials and achieve similar prediction accuracies as multivariate pattern classification of voxel activities in frontopolar cortex. We discuss implications of our findings and suggest a simple way to improve analyses of fMRI BOLD signals to contain effects of sequential dependencies between trials.